1995
DOI: 10.20870/oeno-one.1995.29.4.1119
|View full text |Cite
|
Sign up to set email alerts
|

Plastids, starch and chlorophyll in <em>Vitis vinifera</em> L. berry during its ontogenesis

Abstract: <p style="text-align: justify;">Structural and ultrastructural investigations on plastidial ontogenesis in the tissues of <em>Vitis vinifera</em> berry arc realised in narrow association with starch and chlorophyll dosages from the stage of fruit setting till berry ripeness. During the whole of that period, some chloroplasts, starch and chlorophyll arc noted in grape berry.</p><p style="text-align: justify;">Well developed starch chloroplasts and a great deal of chlorophyll are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Because chlorophyll concentrations in grapes decline during ripening ( ), chlorophyll fluorescence determinations could also be another nondestructive way to examine grape ripening because the intensity of chlorophyll fluorescence emanating from a tissue is almost certainly influenced by the chlorophyll concentration. Chlorophyll fluorescence measurements are not only noninvasive but are simple and rapidly taken, and portable chlorophyll fluorometers for field measurements are now readily available ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…Because chlorophyll concentrations in grapes decline during ripening ( ), chlorophyll fluorescence determinations could also be another nondestructive way to examine grape ripening because the intensity of chlorophyll fluorescence emanating from a tissue is almost certainly influenced by the chlorophyll concentration. Chlorophyll fluorescence measurements are not only noninvasive but are simple and rapidly taken, and portable chlorophyll fluorometers for field measurements are now readily available ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…If so, this would contrast greatly with foliar assimilation, suggesting major differences in the metabolic activity of the plastids. To date in grape berries, only the ultrastructure of plastids have been presented ( Fougere-Rifot et al, 1995 ), however, a recent study of the bioenergetics of tomato chromoplasts demonstrated significant functional rearrangement of electron transport ( Renato et al, 2014 ), which may suggest that sulfur assimilation is also altered.…”
Section: Sulfur Dioxide Assimilation and Metabolism In The Berrymentioning
confidence: 99%